POWER SUPPLY RESTORATION IN ACTIVE DISTRIBUTION NETWORKS WITH HIGH PHOTOVOLTAIC PENETRATION BASED ON SOFT OPEN POINTS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
A fundamental concern for the proper functioning of active distribution networks (ADNs) is the continuity of energy supply service. The soft open point (SOP), a device based on power electronics consisting in back-to-back voltage source converters (VSC), represents a flexible solution to improve the performance of ADNs and enhance the service restoration rate in fault conditions. This paper proposes an optimization model based on mixed-integer second-order cone programming to efficiently operate multiple SOPs in order to increase the restoration capability. The performance achieved by SOPs using the proposed model is evaluated for the modified IEEE-33 and IEEE-69 bus systems, considering high photovoltaic (PV) penetration and various load and generation scenarios. The obtained results show improvement in the service restoration rate (by up to 20 %) when SOPs are installed in the ADN.
Keywords: Active distribution network; Renewable energy sources; Soft open point; Supply restoration; Photovoltaic (PV)